2019
DOI: 10.1021/acsomega.9b01488
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition Growth of Silicon Nanowires with Diameter Smaller Than 5 nm

Abstract: Quantum confinement effects in silicon nanowires (SiNWs) are expected when their diameter is less than the size of the free exciton (with a Bohr radius ∼5 nm) in bulk silicon. However, their synthesis represents a considerable technological challenge. The vapor–liquid–solid (VLS) mechanism, mediated by metallic nanoclusters brought to the eutectic liquid state, is most widely used for its simplicity and control on the SiNWs size, shape, orientation, density, and surface smoothness. VLS growth is often performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…CNTs are grown using several methods, such as arc discharge, laser ablation, and chemical vapor deposition (CVD). CVD technique is more effective as it is a cost-effective technique and provides high-purity material under controlled growth conditions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…CNTs are grown using several methods, such as arc discharge, laser ablation, and chemical vapor deposition (CVD). CVD technique is more effective as it is a cost-effective technique and provides high-purity material under controlled growth conditions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage is the possibility to obtain Si NWs with a diameter down to about 10 nm as shown by Lieber’s group [ 5 ] and even below this limit. Recently, Puglisi et al demonstrated the realization of Si NWs with a diameter under 10 nm by varying the plasma power and the gas pressure in a VLS process realized by a plasma enhanced chemical vapor deposition [ 40 ]. However, their synthesis is still complex and the Si NWs showed in these papers have different orientations making more complex their implementation for real applications.…”
Section: State Of Art Of Si Nw Synthesismentioning
confidence: 99%
“…However, their synthesis is still complex and the Si NWs showed in these papers have different orientations making more complex their implementation for real applications. Hence, even if it is possible to reach less than 10 nanometer in diameter, it leads to a lack of orientation control of the Si NW growth [ 40 , 41 ].…”
Section: State Of Art Of Si Nw Synthesismentioning
confidence: 99%
“…Developing quantum size Si nanowires (SiNWs) is of interest for different optoelectronic and photovoltaic applications. [1][2][3][4] Si nanowires with a diameter below 10 nm have a bandgap that increases as their diameter decreases. [5] Interestingly, they can also adopt the metastable hexagonal diamond crystalline structure, [6] the calculated electronic structure of which would have specific and interesting opto-electronic properties (increased absorption).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have achieved the synthesis of small diameter SiNWs, using well-defined gold nanoclusters as catalysts in a vapor-liquid-solid (VLS) growth process or in a supercritical hexane solution phase. [3,[8][9][10] However, these methods deliver a small fraction of NWs with sufficiently small diameters. Moreover, the use of gold brings undesirable impurities.…”
Section: Introductionmentioning
confidence: 99%